أثر التدفقات النقدية على عوائد أسهم البنوك الخاصة في سورية - الحجلة, مجد (Latakia University Journal - Economic and Legal Sciences Series, 2018)
هدفت الدراسة إلى اختبار العلاقة بين كل من التدفقات النقدية من الأنشطة التشغيلية والأنشطة الاستثمارية والأنشطة التمويلية والأنشطة مجتمعة وبين عوائد الأسهم للقطاع المصرفي الخاص في سورية وتكونت عينة الدراسة من ثمانية مصارف خلال الفترة الممتدة بين عام 2006م وعام 2011م، وقد تم فحص العلاقة بين التدفقات النقدية وعوائد الأسهم باستخدام نموذج الانحدار الخطي المتعدد. وخلصت الدراسة إلى عدة نتائج أهمها، عدم وجود علاقة بين كل من التدفقات النقدية من الأنشطة التشغيلية والتدفقات النقدية من الأنشطة التمويلية، والتدفقات النقدية من الأنشطة مجتمعة ، وبين عوائد الأسهم لبنوك القطاع المصرفي الخاص في سورية، كما تبين وجود علاقة عكسية ذات دلالة احصائية بين التدفقات النقدية من الأنشطة الاستثمارية وبين عوائد الأسهم لبنوك القطاع المصرفي الخاص في سورية. كما لوحظ تدني القيمة التفسيرية لنموذج الدراسة إذ أن العوامل المستقلة قادرة على تفسير التغير في تحديد قيمة الأسهم المتداولة بنسبة 8.1% فقط . وأوصت الدراسة بضرورة إيلاء قائمة التدفقات النقدية أهمية أكثر وتوجيه مستخدمي القوائم المالية إلى فهمها وتحليلها كونها توفر معلومات مالية خالية من التضليل، كما يفضل استخدام الطريقة المباشرة في إيجاد التدفقات النقدية من الأنشطة التشغيلية لأنها تفصح عن كل مصدر من مصادر النقدية وكيف أنفق في النشاطات التشغيلية كما أوصى بها المعيار المحاسبي الدولي رقم (7) كونها تقدم معلومات مفيدة في تقدير التدفقات النقدية المستقبلية. This study aimed to test the relationship between each of cash flows from operating activities, investment activities, financing activities and joint activities; all together with dividends of Private banking sector in Syria. The study sample consisted of eight banking during the period 2006-2011. The relationship between cash flows and stock returns has been examined by using of regression analysis. The study results indicated to the absence of any relationship between each of: cash flows from operational activities, cash flows from finance activities and cash flows from joint activities; and shares' returns of all banks, also showed to the existence of negative relationship between cash flows from investment activities and shares' returns of all banks. It was also noted the low explanatory value of the model study as independent factors able to explain the change in determining the value of shares traded increased by only 8.1%. The study recommended to pay more attention to cash flows statement, and to direct financial statements users to be able both to understand and analyze it, to get the most benefit from it, Also prefer to use the direct method to find the cash flows from operating activities as they disclose the source of all sources of cash and how it was spent on operating activities as recommended by the International Accounting Standard No. (7) Being provided useful information in estimating future cash flows.